Nurses' and student nurses' inferences of pain and psychological distress - Allcock, Nicholas John (1997)
Poor pain assessment contributes to inadequate postoperative pain relief. Studies in the US suggest that nurse education might make students less sensitive to patients' experience of pain. This research set out to examine this process in the United Kingdom and to explore the experience of the students during their common foundation programme (CFP). 217 students completed the Standard Measure of Inferences of Suffering Questionnaire (SMIS) before and after their CFP. Their inferences of psychological distress increased as studies in the US had found but unlike these studies no change was found in their inferences of pain. Inferences of pain and psychological distress were affected by the age of the cases, while gender affected only the latter. None of the characteristics of the students were related to their inferences